2002
DOI: 10.1006/jcta.2001.3223
|View full text |Cite
|
Sign up to set email alerts
|

Binary Partitions Revisited

Abstract: The restricted binary partition function b k (n) enumerates the number of ways to represent n as n=2We study the question of how large a power of 2 divides the difference b k (2 r+2 n) − b k − 2 (2 r n) for fixed k \ 3, r \ 1, and all n \ 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…(A similar family of congruences for a restricted binary partition function was also proved by Rødseth and Sellers [2].) With the above in mind, we can shed more direct light on our goal for this note by first proving the following two infinite families of divisibility properties modulo 2 satisfied by b(n).…”
Section: Theorem 2 ([5] Theorem 2) the Generating Function For B(n) supporting
confidence: 52%
“…(A similar family of congruences for a restricted binary partition function was also proved by Rødseth and Sellers [2].) With the above in mind, we can shed more direct light on our goal for this note by first proving the following two infinite families of divisibility properties modulo 2 satisfied by b(n).…”
Section: Theorem 2 ([5] Theorem 2) the Generating Function For B(n) supporting
confidence: 52%
“…For m = 2, this is essentially Theorem 3.6 in Reznick [12]. In a series of papers (see [13,14] and the references therein) it has been shown that b m,k (n) possesses certain divisibility properties. From Section 3 we now get divisibility properties of a rather different type.…”
Section: A Special Case: M-ary Partitionsmentioning
confidence: 91%
“…A number of proofs of (1.2) have been given by several authors; cf. [4]. Families of congruences also appear in the literature for the m-ary partition function which are valid for any m ≥ 2; cf.…”
Section: Introductionmentioning
confidence: 99%